2021
DOI: 10.3389/fenvs.2021.719274
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Occurrence in Surface Waters and Sediments in Five River Mouths of Manila Bay

Abstract: Microplastics have been increasingly documented globally in numerous environmental compartments. However, little information exists in the Philippines despite the fact that the country is considered to be one of the largest contributors of plastics in oceans. This study, considered as one of the pioneering microplastic research, evaluated the abundance, distribution, and composition of microplastic pollution in the mouths of five rivers, namely Cañas, Meycauayan, Parañaque, Pasig and Tullahan, draining to Mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 96 publications
(109 reference statements)
1
13
0
1
Order By: Relevance
“…Thus, film microplastics can be more detectable in sediment samples than surface water. This observation supports Osorio et al [20] study, as they found that plastic films are uncommon to surface water but more present in their sediments, especially in Mecauayan and Tullahan Rivers.…”
Section: ) Categorization Of Microplastics Through Shapesupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, film microplastics can be more detectable in sediment samples than surface water. This observation supports Osorio et al [20] study, as they found that plastic films are uncommon to surface water but more present in their sediments, especially in Mecauayan and Tullahan Rivers.…”
Section: ) Categorization Of Microplastics Through Shapesupporting
confidence: 89%
“…These are commonly used as food and product containers and as floats and rafts in fishing. According to the study of Osorio et al [20]. Foams are abundant in Mecauayan, and Tullahan Rivers compared to other main rivers connected in Manila Bay from October 2018 to March 2019.…”
Section: ) Categorization Of Microplastics Through Shapementioning
confidence: 99%
See 2 more Smart Citations
“…2022 yılında Pakistan, Rawal Gölü'ndeki siyah MP'lerin, diğer renklere göre %25 ile %48 arasında daha baskın olduğu ve siyah MP'lerin lastikler, plastik torbalar ve sentetik tekstil ürünlerinden kaynaklanabileceği ifade edilmiştir (Alfonso et al, 2020;Nousheen et al, 2022). Yapılan çalışmalarda, balıkların yanlışlıkla planktonik avlarına benzeyen beyaz, kahverengi ve sarı renklere sahip MP'ler ile beslendiği (Shaw & Day, 1994;Boerger et al, 2010;Osorio et al, 2021) benzer şekilde deniz kuşlarının da bazı şekil ve renklerde plastikleri yanlışlıkla yuttuğu tespit edilmiştir (Barboza & Gimenez, 2015;Osorio et al, 2021).…”
Section: Mikroplastiklerin Morfolojik öZelliklerine Göre Dağılımlarıunclassified